2017
DOI: 10.1136/medethics-2016-103990
|View full text |Cite
|
Sign up to set email alerts
|

The ethics of betel nut consumption in Taiwan

Abstract: The ethics of betel nut use in Taiwan are examined in this article. It first presents scientific facts about the betel quid, its consumption and negative health consequences and then analyses the cultural background and economic factors contributing to its popularity in Asia. Governmental and institutional attempts to curb betel nut cultivation, distribution and sales are also described. Finally, the bioethical implications of this often ignored subject are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…BQ chewing peaked in the 1980s, and consumption increased 10-fold from 1992 to 2011. Areca nut cultivation expanded considerably, with a 58-fold increase in the number of plants grown from 1981 to 1990, while only 4% of its production was for export [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…BQ chewing peaked in the 1980s, and consumption increased 10-fold from 1992 to 2011. Areca nut cultivation expanded considerably, with a 58-fold increase in the number of plants grown from 1981 to 1990, while only 4% of its production was for export [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Areca nut grows in several country such as Indonesia, Malaysia, India, Bangladesh, China, etc. Traditionally, areca nut are used for some medical use [46,47]. The major chemical properties of Areca nut are polyphenols (flavonoids and tannin), polysaccarides, proteins, fats, fibers, alkaloids, minerals, vitamin B and C [48].…”
Section: Evaluation Of Epithelial Thickness On Proliferation Phase Ofmentioning
confidence: 99%
“…Several previously reported studies have also demonstrated the relationship between and betel quid chewing and liver diseases such as liver fibrosis, liver cirrhosis, and even hepatocellular carcinoma (HCC) (13)(14)(15). Considering the harmful effect of betel quid chewing on human health and the negative impact of A. catechu on the environment, especially on soil and water conservation, cultivation of A. catechu is being discouraged by Taiwan government (16).…”
Section: Introductionmentioning
confidence: 99%